MicroRNA-138 Abates Fibroblast Motility With Effect on Invasion of Adjacent Cancer Cells - Rajthala, Saroj; Parajuli, Himalaya; Dongre, Harsh Nitin; Ljøkjel, Borghild; Hoven, Kristin Marie; Kvalheim, Arild; Lybak, Stein; Neppelberg, Evelyn; Sapkota, Dipak; Johannessen, Anne Christine; Costea, Daniela-Elena (Frontiers in Oncology, 2022)
Background: Recent studies showed aberrant expression of micro-RNAs in cancer-associated fibroblasts (CAFs). This study aimed to investigate miR-138 dysregulation in CAFs in oral squamous cell carcinoma (OSCC) and its effects on their phenotype and invasion of adjacent OSCC cells. Methods: Expression of miR-138 was first investigated in OSCC lesions (n=53) and OSCC-derived CAFs (n=15). MiR-138 mimics and inhibitors were used to functionally investigate the role of miR-138 on CAF phenotype and their ability to support OSCC invasion. Results: Expression of miR-138 showed marked heterogeneity both in OSCC tissues and cultured fibroblasts. Ectopic miR-138 expression reduced fibroblasts’ motility and collagen contraction ability, and suppressed invasion of suprajacent OSCC cells, while its inhibition resulted in opposite outcome. Transcript and protein examination showed that the anti-tumour effect of miR-138 in CAFs was mediated via focal adhesion kinase axis and TGFβ1 signaling pathway. Conclusions: Despite its heterogeneous expression, miR-138 in OSCC-derived CAFs exhibits a tumour suppressive function.